(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
Sound is born as a signal and through it we learn about the internal construction of reality without destroying it. All sounds tell us. The ‘things of sound’ pass through us and then become a text-world and a vector of dynamic imagination that makes it the starting point for any form of composition. With the project #restaCorale by artist-psychologist Luigi Pagliarini, born during the Covid-19 emergency, sound becomes an essential component of artistic expression within the immense concert of lives. Its “Manifesto per un’arte Corale” stems from a condition of concrete rebirth, overcoming any individualism and with the ambition to go beyond the anthropocentric dimension. Pagliarini attempts to build an artistic community of 130 students of the ABAMC (Academy of Fine Arts of Macerata), who have each executed six works responding to the actions #restaUmano, #restaCasa, #restaSicuro, #restaCreativo and #restaTeStesso representing some important moments experienced during the quarantine. This practice of rehumanisation of the creative-choral action is imagined and conceived by Luigi Pagliarini, as well as accompanied by a further project #restaInAscolto, i.e. an environmental sampling of variable length from 10 to 60 seconds of audio recordings of the domestic environment, from the preparatory gestures of the actions required to the sound produced by the artistic gesture itself. This multiform, gigantic work, after the untimely death of the artist Pagliarini, gives us the responsibility to continue his work. Our ‘pre-tension’ is precisely that of starting again from the sound that becomes a pre-existing, archived choral composition, but with the need (ours) to recover our breath and to be able to compose a new ‘sound mosaic’ just imagined until arriving at Pianeta-Mente, the last work written by Pagliarini, a fable that is in tune with the profound meaning of chorality and necessary recovery.